Special Educational Needs Coordinators' Practice in England 40 Years on From the Warnock Report - Esposito, Rosanne; Carroll, Catherine (Frontiers in Education, 2019)
The Special Educational Needs Coordinator (SENCO) role in England has been formally established since 1994 to support inclusion. In 2009 it became mandatory for every new SENCO in a mainstream school in England to gain a postgraduate qualification in special educational needs coordination within three years of taking up a post, which includes a compulsory practitioner research component. This study examined 100 assignment abstracts from 50 SENCOs submitted as part of the postgraduate qualification delivered in one university in England between 2015 and 2017. Data were analysed using thematic analysis in Nvivo and yielded four principles underpinning SENCO practice at pupil and whole school levels including diversity in SENCO practice, meaningful assessment, evidence-informed practice and evaluating impact. The findings are discussed in the light of developments in policy and practice in the education of pupils with special educational needs and/or disabilities since the Warnock Report in 1978.